Image Instabilities and Polarization Crosstalk - R. Casini; A. G. de Wijn (The Astrophysical Journal)
We expand on our previous study of the impact of atmospheric seeing on polarization crosstalk, and show how the formalism that was developed in that work can be applied to treat the case of spatial modulators of polarization. Beside formally demonstrating how the problem of crosstalk is fully eliminated in such devices, we also gain insight on the meaning of polarimetric noise of temporal modulation schemes in the limit of very high modulation frequency. We also describe the problem of spectrograph instabilities, and how the spectral gradients that are naturally associated with a line spectrum feed into the problem of polarimetric errors induced by mechanical vibrations, thermal drifts, and pointing jitter. Finally, we show how this formalism can be used to estimate the contribution of polarization crosstalk to the errors on the elements of the 4 × 4 Stokes response matrix, for the purpose of producing realistic error budgets for polarimetric instrumentation.